Pengaruh Fasilitas Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Divisi Produksi Pada PT. Meccaya Bekasi - Mochammad Hermawan; Jeni Andriani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study is to determine the extent of influence of work facilities and work motivation on the performance of employees in the production division at PT. Meccaya Bekasi, and to analyze both partially and simultaneously. The type of research used in this study is quantitative research with an associative approach.The population in this study were 50 employees of the production division at PT. Meccaya Bekasi, while the sample in this study used a saturated sample, namely 50 employees of the production division who worked at PT. Meccaya Bekasi, Data analysis used validity, reliability, classical assumptions, linear regression, correlation coefficient, determination coefficient, and hypothesis testing with the help of the SPSS 27 program. The results of the study showed that Work Facilities partially influenced Employee Performance, this can be proven by the results of the hypothesis test obtained a value of t count> t table or (14.063> 1.669) This is also explained by the value of ρ value <Sig.0.05 or (0.000 <0.05) with the regression equation Y = 5.105 + 0.879X1 and the results of the correlation coefficient test of 0.897 and the results of the determination coefficient test obtained an Adjusted R-Square value of 0.801 or 80.1%. Partially, Work Motivation has an effect on Employee Performance, this can be proven by the results of the hypothesis test obtained a calculated t value > t table or (17.080 > 1.669). This is also moderated by the value of ρ value < Sig.0.05 or (0.000 < 0.05) with a simple linear regression equation Y = 5.085 + 0.873X2, then the results of the correlation coefficient test are 0.927 and the results of the determination coefficient test are 0.856 or 85.6%. Simultaneously, Work Facilities and Work Motivation have an effect on Employee Performance with the results of the hypothesis test obtained a calculated F value > F table or (149.585 > 3.15), this is also moderated by the p value < Sig.0.05 or (0.000 < 0.05) with the multiple linear regression equation Y = 4.509 + 0.678X1 + 0.215X2, and the results of the correlation coefficient test are 0.930 and the results of the determination coefficient test are 0.858 or 85.8%.